Shewanella putrefaciens, a rare human pathogen: A review from a clinical perspective - Müller, Stephanie; von Bonin, Simone; Schneider, Ralph; Krüger, Martin; Quick, Susanne; Schröttner, Percy (Frontiers in Cellular and Infection Microbiology, 2023)
Shewanella putrefaciens is a gramnegative, facultatively anaerobic, rod shaped bacterium. It belongs to the class of the Gammaproteobacteria and was first described in 1931. S. putrefaciens is part of the marine microflora and especially present in moderate and warm climates. The bacterium is a rare oppurtonistic human pathogen associated mainly with intra-abdominal as well as skin and soft tissue infections. However, it has also been reported in association with more severe diseases such as pneumonia, intracerebral and ocular infections and endocarditis. In these cases the clinical courses are often associated with underlying, predisposing diseases and risk factors. For successful treatment of S. putrefaciens, a combination of appropriate local therapy, e.g. surgical treatment or drainage, and antibiotic therapy should be performed. Since multiple resistances to antibiotics are described, the results of the antimicrobial susceptibility testing must be considered for effective therapy as well. Furthermore, a main challenge in clinical practice is the accurate microbiological identification, and especially the correct differentiation between S. putrefaciens and S. algae. Under certain circumstances, Shewanella-infections can have severe, sometimes even fatal consequences. Therefore, we decided to present the current state of knowledge as well as further aspects with regard to future diagnostics, therapy and research.